Perceptions of Malay Language Teaching Challenges and Digital Game Integration Among Primary School Teachers in Malaysia - Feng, Koo Lee; Tze Jin, Wong; Naning Zin, Fatin Hana binti; Mohd Yusof, Farah Hanim binti (Journal of Neonatal Surgery, 2025)
Teachers’ perceptions of the challenges faced by students in learning the Malay language and their attitudes toward the integration of digital game-based learning tools were explored. A quantitative study design is employed to collect the data via a Likert-scale questionnaire distributed to 400 teachers from urban and suburban schools in Malaysia. A purposive sampling technique was used to ensure participants had relevant expertise, while random selection was utilized within this cohort to enhance representativeness. Descriptive analysis revealed that teachers identified several persistent challenges in students’ language acquisition, including limited vocabulary, low confidence in speaking, and difficulties with writing and reading. Notably, student motivation was reported as the lowest among key domains. Despite these challenges, teachers expressed strong support for incorporating digital game-based learning to enhance vocabulary retention and student engagement. However, multiple linear regression analysis indicated no statistically significant relationship between teachers’ perceptions of student challenges and their support for digital tools, suggesting that external factors—such as institutional policy or digital literacy—may play a larger role in shaping teachers’ readiness to adopt technology. Further, teachers ranked grammar and vocabulary as the most two important components for integration into Game-Based Learning (GBL) environments. Comparisons with a similar Arabic language study revealed alignment in instructional priorities, particularly regarding the foundational role of vocabulary and grammar. These findings underscore the need for pedagogically grounded, tech-enhanced learning solutions that directly address core language challenges while aligning with broader educational strategies.